Need Analysis of Prospective Science Teachers about Pedagogical Content Knowledge through Learning Activities - Sehrish Khan; Rabia Mumtaz; Sumaira Batool (National University of Modern Languages (NUML), Islamabad, 2023)
Pedagogical  Content  Knowledge  (PCK)  is  a  blend  of  content  knowledge  and pedagogy  knowledge,  which  can  illustrate  the  ability  of  teachers  to  design  and to  teach  a  content  by  accessing  what  they  knows  about  the  material,  students, curriculum  and  how  best  to  teach  the  content.  PCK  develop  in  learners  through  different  learning  activities  so  that  when  they  come  in  passion  they deal  more  effectively  with  students. The   objectives of   study were ;to  find  out the  need  of  Pedagogical  Content  Knowledge  in  Prospective  Science  Teachers,  to  explore  the  Pedagogical  Content  Knowledge  in  prospective  Science  Teachers,  to  evaluate  the  performance  of  Prospective Science Teachers  through  Pedagogical  Content  Knowledge  and  to  compare  the  Pedagogical  Content  Knowledge  of  Prospective  Science  Teachers  at  IIUI  and  NUML.  This  study focused  on  "Need  Analysis of  Prospective  Science  Teachers  about  Pedagogical  Content  Knowledge  through learning  activities". The random   sampling   technique was used to conduct the study. The study was   delimited to the public universities of Islamabad. To achieve objectives of the study mixed method research approach was selected. Keeping in view the research method, survey was conducted through self-developed questionnaire. Furthermore, semi-structure interview were also drawn. Descriptive and Inferential Statics was  used  to  analyze  data.